Membangun Service Attitude yang Efektif: Pendekatan Psikologi Sosial di Dinas Kependudukan Kota Palembang - Mawardah, Mutia; Naura Nasiwa, Mafanda (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
Quality public services are not only determined by an efficient administrative system, but are also greatly influenced by the attitudes and behavior of officers in interacting with the public. This study aims to evaluate and improve the service attitude of employees of the Population and Civil Registration Service (Disdukcapil) of Palembang City through a social psychology approach. Problems faced in the field include low empathy, lack of interpersonal communication skills, and the failure to form a responsive service culture. The methods used in this study include participatory observation, in-depth interviews with employees and service users, and training based on social psychology theory that emphasizes the importance of two-way communication, strengthening empathy, and understanding the dynamics of social interaction. The training was carried out in the form of an interactive workshop accompanied by service simulations and feedback from the public. The results showed a significant increase in terms of empathetic attitudes, speed of response to service requests, and politeness in communication. Employees also showed higher work motivation and a better understanding of their social roles in public services. These findings reinforce that a social psychology approach can be an effective strategy in forming a more humanistic, adaptive, and sustainable service culture.